The Influence of Employee Work Culture on Service Quality at the Regional Drinking Water Company of Tirta Gerbang Emas, North Gorontalo Regency - Yulianti G. Lamato (Formosa Journal of Applied Sciences, 2023)
This study aims to determine the effect of employee work culture on service quality at the Tirta Emas Regional Drinking Water Company (PDAM) in North Gorontalo Regency. The population in this study were all employees or employees at the PDAM Tirta Emas Office, Gorontalo Regency, totaling 54 people, and the community as customers was directly determined to be 20. In this study the researcher used a correlational descriptive test technique with data collection tools for both variables namely observation, questionnaires, and interviews.Based on the results of data analysis the results obtained included, the form of the linear regression equation Y ̂ = 11.77 + 0.71x, and the price of the correlation coefficient (r) is obtained r = 0.751 with a determination coefficient r2 = 0.564 or 56.4% variable Y is influenced by variable X, while the remaining 43.6% is influenced by other factors such as discipline and leadership.The results of testing the significance of the correlation coefficient show that > ​​namely 9 .91 > 2.00 which proves that the correlation coefficient between variable X and variable Y is significant (meaningful). And from the analysis carried out, the research hypothesis that is "there is a significant influence of employee work culture on service quality" is accepted at a significant level = 0.05.